THE EFFECT OF PROBLEM-BASED LEARNING MODEL ON ADAPTIVE REASONING ABILITY IN MATHEMATICS CLASS V ELEMENTARY SCHOOL - Wahyuni, Rulanda Zahra; Widyasari, Nurbaiti (FKIP Universitas Muhammadiyah Tangerang, 2025)
The primary aim of this study is to enhance students' adaptive reasoning ability by applying the problem-based learning model. The chosen method, a pseudo-experiment with a non-equivalent control group design, was selected for its rigorous approach, instilling confidence in the research process. The population consisted of 105 students in class V, with a sample of 41 students selected, divided into 21 students in the control class and 20 in the experimental class, determined by the purposive sampling technique. The instrument used was a test to assess adaptive reasoning skills. The data analysis, conducted with an independent T-Test, revealed that the adaptive reasoning ability with the PBL model was higher than that of students who applied the expository learning model. These findings, based on a robust methodology, suggest that the PBL model has the potential to significantly enhance students' adaptive reasoning skills in mathematics.